Femtosecond laser-assisted cataract surgery in patients with phakic intraocular lenses and low endothelial cell counts: a case report - Chia-Yi Lee; Shih-Chun Chao; Chi-Chin Sun; Hung-Yu Lin (BMC Ophthalmology, 2017)
Abstract Background Phakic intraocular lens (PIOL) implantation has been used to correct myopia and myopic astigmatism, although corneal decompensation can occur after implantation. Femtosecond laser-assisted cataract surgery (FLACS) has gained in popularity due to its lower postoperative astigmatism and endothelial loss. Herein, we report the use of FLACS in patients who previously received PIOL implantation and have a low corneal endothelial cell count. Case presentation Two patients with a previous iris-claw PIOL implantation were enrolled. The preoperative corrected distance visual acuity (CDVA) and diopter sphere (DS) were 20/32 and −0.25 D in patient 1 and 20/32 and −3.00 D in patient 2. Specular microscope examination revealed an endothelial cell density (ECD) of 1532/mm2 in patient 1 and 1620/mm2 in patient 2. Capsulotomy was performed smoothly using a femtosecond laser. Postoperative CDVA improved in both eyes, with a difference of DS less than 1 D from the preoperative estimation. Specular microscope examination revealed a decreased endothelial cell density (ECD) in patient 2, but no signs of corneal decompensation were detected. Conclusions The influence of using PIOL on capsulotomies performed via FLACS, in combination with preoperative refraction calculation, is minimal. A mild decrease in ECD may occur, but there is a low probability of severe corneal decompensation, even in patients with a low endothelial cell count.